Language, Mass Media, and Democracy: The Debate over "Kalimah Allah" in The Malaysian Print and Online Media - Eva Eichenauer (Kajian Malaysia, 2016)
Through a comparative media analysis, this paper examines the media coverag of the print dailies Utusan Malaysia and The Star as well as the online news site MalaysiaKini on the debate over kalimah Allah that gained momentum in early 2010, when the High Court allowed Christians in Malaysia to use the term Allah for addressing God in their religious services and publications. A systems theoretical approach is used to study the interrelation of mass media and the political system. Although one might assume that because of the highly controlled print media, Malaysia's realities are challenged only via "online dissent", this study suggests that Malaysia's linguistically plural public sphere offers multiple re-presentations of reality even within the highly restricted context print publications operate in. It also shows that the print media landscape not only reflects and reproduces the ethnic-based division of Malaysia's political system, but is a key player in actively creating the ethnic division of Malaysian societythat is crucial for the ruling coalition to stay in power. Hence, this paper argues that, even though technological innovations do offer spaces to create alternative realities, in a multi-lingual national context as in Malaysia, the interrelation between language and news content is an even more crucial element of constructing shared knowledge and collective identities.